Onset of methanogenesis in landfilled MSW. - Barry, D. L.; Smith, Richard; Harries, C. (The Waste Conference Limited, 2004)
This research project (Barry et al. 2003, 2004a and 2004b) assessed the time period for the onset of methanogenesis and examined the scale of methane (CH4) fluxing from waste surfaces during the waste placement phases before gas control systems were installed. The gas regime at one landfill site was monitored over a 16-month period via a series of probes and perforated pipes installed at three different layers as waste disposal operations progressed. Bulk gas concentration data demonstrated that methanogenesis was evident after only ~ 1-2 months, with the CH4/CO2 ratio increasing to >1 after ~ 5-6 months from commencement of waste filling. The gas flux from lower waste levels did not appear to influence the period for onset of methanogenesis in the upper, shallower waste layers. This reinforces the conclusion established from overall surface fluxing patterns that higher horizontal gas permeability of the wastes provides the preferential pathway. Surface CH4 flux was detected within ~ 1 month after waste placement.